Reputasi Kantor Akuntan Publik, Prediksi Kebangkrutan, Profitabilitas dan Audit Delay - Maharani, Ni Luh Komang Winda Sindu; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 31 No 8 (2021)DO - 10.24843/EJA.2021.v31.i08.p18, 2021)
The lengthy audit process will affect the timeliness in the publication of financial statements to the public. The delay in publication will reduce the benefits of the company's financial statements, so knowledge is needed about the factors that affect audit delay. The purpose of this study was to determine the effect of public accounting firm reputation, bankruptcy prediction, and profitability on audit delay. This research was conducted in mining sector companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The research sample was selected using a purposive sampling method as many as 40 companies were studied over a 3 years period using annual financial statements. Data collection methods and data analysis techniques used are non-participant observation methods and multiple linear regression analysis. The results of this study indicate that the reputation of a public accounting firm has a negative effect on audit delay, bankruptcy prediction has a negative effect on audit delay, and profitability has a negative effect on audit delay. Keywords: Public Accounting Offices; Bankruptcy Prediction; Profitability; Audit Delay.